Navigating Healthcare Decision Dynamics Among Physicians: Transforming Pharma Marketing Strategies from Rationality to Resonance. - Athanasiou, Alexandros (Digital Repository of Theses, 2025)
The pharmaceutical industry faces significant challenges, within an environment that is getting increasingly competitive, where research and development costs that are constantly increasing, and many new treatments have low clinical differentiation. Traditional marketing approaches, which are mostly focused on the communication of product characteristics, find it challenging to differentiate brands. This research investigates the impact of emotional branding on physicians' prescribing choices and provides a practical framework for pharmaceutical companies to evolve their marketing strategies from primarily data-driven narratives to emotionally resonant engagement. This research uses a mixed-methods approach, combining qualitative questionnaire, focus groups with senior pharmaceutical marketing experts across the globe, and case studies analysis of successful emotional branding examples. The findings indicate that although clinical data is important, other factors such as trust, empathy, and personal values, can significantly influence treatment decisions. Emotional resonance can strengthen brand preference, build loyalty, and build physician advocates, reinforcing the brand’s competitive advantage. Several barriers to the adoption of emotional branding were identified, including internal organizational resistance, regulatory constraints, and the industry's traditional reliance on rational product messaging. Participants stressed the challenge of balancing emotional storytelling with ethical communication, emphasizing the need for marketing strategies that are both engaging and scientifically accurate, while adhering to industry rules. Despite these challenges, the research reveals significant opportunities to increase brands differentiation, particularly in highly competitive markets where clinical characteristics are comparable across competitive brands. The research concludes with a systematic framework for incorporating emotional elements into pharmaceutical marketing strategies. The resulting framework can hopefully support pharmaceutical companies to cultivate a culture that prioritizes emotional connection along with clinical excellence, to identify and leverage emotional drivers and ultimately develop emotionally compelling narratives that will help establish deeper relationships with healthcare professionals and patients.